DEVELOPMENT OF METHODS FOR DETERMINATION OF SPECIFIC IMPURITIES IN THE GLUTATIONION RESTORED SUBSTANCE - K. A. Alexeeva; D. I. Pisarev; A. Yu. Malyutina; N. N. Boyko (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
Glutathione (γ-L-glutamyl-L-cysteinylglycine) is the most important low molecular weight intracellular thiol tripeptide consisting of three amino acids - glycine, cysteine and glutamic acid. In Russian pharmacopoeia there is no regulatory documentation for glutathione, therefore, the development of a pharmacopoeial item for the specified substance is a relevant problem.The aim of the article is the development of methods for determining foreign specific impurities in glutathione.Materials and methods. The substance of glutathione reduced (CAS 70-18-8, EC 2007254, Applichem, Germany) containing impurities, and a standard sample of reduced glutathione (Sigma Aldrich, Japan) were used as the objects of the study. The analysis was carried out by using a high-performance liquid chromatography method in the reverse phase version and a thin layer chromatography method. The chromatography using RP HPLC was performed after preliminary derivatization of glutathione and its specific impurities with dancil chloride. Specific impurities in glutathione are dipeptides and amino acids. Therefore, they, like glutathione, can react with dancil chloride. Dancil derivatives are formed, and they can be determined by chromatographic separation.Results. As a result of chromatography by the method of RP HPLC of derivatized dancil chloride glutathione it has been established that this reaction makes it possible to detect impurities in it. Glutathione derivatives are well separated by chromatography by implementing the method of RP HPLC and have different absorption maxima. The glutathione derivative had an absorption maximum at λmax=284 nm. The derivatives belonging to specific glutathione impurities absorb at λmax=288 nm and λmax=296 nm. The data obtained using RP HPLC were confirmed by TLC in the isopropanol-water (2:1) system. Three components were found out, one of which corresponds to glutathione, while two others are impurities.Conclusion. Methods for determining impurities in the glutathione substance using RP HPLC methods with preliminary derivatization with dancil chloride and TLC with ninhydrin detection have been worked out. A comparative analysis of the data obtained makes it possible to state that the OF-HPLC method with pre-column derivatization is more reliable, since it is more sensitive to impurities, and also makes it possible to study the UV profiles of impurity components better than the TLC method. Therefore, for the detection of impurities in the substance of glutathione, it is more preferable to use RP-HPLC with pre-column derivatization. The results of this study can be recommended for inclusion in the regulatory documentation on the substance of glutathione in the section "Impurities".